KECEMASAN MATEMATIKA DAN SELF EFFICACY DALAM MELAKUKAN PEMBUKTIAN MATEMATIKA - Dwi Yanti; Herma Yunita (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2020)
Self-Efficacy or a lack of confidence is one of the causes of mathematical anxiety. This paper discusses the best way to overcome mathematical anxiety, self efficacy in proving mathematics. The method used is literature review. Self efficacy has an important role in eliminating the anxiety of mathematics, where if someone has confidence in their abilities, they will be more happy and active in proving mathematics. But sometimes most do not believe or believe in themselves so they tend to be lazy in doing mathematical proof, therefore a learning community is needed where they are able to interact and exchange ideas so that they can open up opportunities to be able to prove mathematics without the math anxiety.